An Entamoeba-Specific Mitosomal Membrane Protein with Potential Association to the Golgi Apparatus - Santos, Herbert J. (Genes (Basel), 2019)
The aerobic mitochondrion had undergone evolutionary diversification, most notable among lineages of anaerobic protists. Entamoeba is one of the genera of parasitic protozoans that lack canonical mitochondria, and instead possess mitochondrion-related organelles (MROs), specifically mitosomes. Entamoeba mitosomes exhibit functional reduction and divergence, most exemplified by the organelle’s inability to produce ATP and synthesize iron-sulfur cluster. Instead, this organelle is capable of sulfate activation, which has been linked to amoebic stage conversion. In order to understand other unique features and components of this MRO, we utilized an in silico prediction tool to screen transmembrane domain containing proteins in the mitosome proteome. Here, we characterize a novel lineage-specific mitosomal membrane protein, named Entamoeba transmembrane mitosomal protein of 30 kDa (ETMP30; EHI_172170), predicted to contain five transmembrane domains. Immunofluorescence analysis demonstrated colocalization of hemagglutinin (HA)-tagged ETMP30 with the mitosomal marker, adenosine-5’-phosphosulfate kinase. Mitosomal membrane localization was indicated by immunoelectron microscopy analysis, which was supported by carbonate fractionation assay. Transcriptional gene silencing successfully repressed RNA expression by 60%, and led to a defect in growth and partial elongation of mitosomes. Immunoprecipitation of ETMP30 from ETMP30-HA-expressing transformant using anti-HA antibody pulled down one interacting protein of 126 kDa. Protein sequencing by mass spectrometry revealed this protein as a cation-transporting P-type ATPase, previously reported to localize to vacuolar compartments/Golgi-like structures, hinting at a possible mitosome-vacuole/Golgi contact site.